FORMATION OF RESPONSE OF RATS ORGANISM ON SINGLE INFLUENCE OF TERIZIDONE - 250 MG + PYRIDOXINE HYDROCHLORIDE - 10 MG - K. A. Badenikova (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The article presents the materials of experimental study of Terizidone in combination with pyridoxine hydrochloride in conditions of single peroral influence on animals in different doses with a view to reveal response of an organism for using in the evaluation of general toxic action of an advanced antituberculous preparation.